One Foe, So Many Fights. Making Sense of Covid-19 Policies - Hubert Kempf (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper develops a tractable model of a society hit by a viral pandemic. It is sufficiently rich so as to relate the optimal decisions of the policymaker to the underlying characteristics of this society, in terms of preferences, social mores and economic structures. This allows us to make sense of the diversity of policies adopted worldwide with respect to the Covid-19 pandemic.
Keywords: E58; E62; F45; H76; 330; Covid-19; public policy; trust; compliance; uncertainty